Treating verbs in aphasia: Exploring the impact of therapy at the single wordand sentence levels - Webster, J.; Whitworth, Anne (John Wiley & Sons Ltd., 2012)
Background: In recent years there has been significant interest in the differential processing of nouns and verbs in people with aphasia, but more limited consideration about whether the differences have implications for therapy. It remains unclear whether verbs can be treated in a similar way to nouns or should be treated using approaches that recognize the relationship between verb retrieval and sentence production. Aims: This paper reviews studies focusing on therapy for spoken verb retrieval, considering the impact of therapy on treated and untreated verbs, sentence production and connected speech. It explores whether there are differential gains across therapy paradigms and whether verbs respond to therapy in the same way as nouns. Method & Procedures: Studies were identified using a systematic search. A total of 26 studies were reviewed and classified under four headings: (1) studies that treated verbs in a single-word context, (2) studies that compared treatment for nouns and verbs, (3) studies that treated verbs in a sentence context, and (4) studies that treated verb retrieval and argument structure. Main Contribution: Findings from the review demonstrate that verb therapy, irrespective of whether verbs are treated within a single-word or sentence context, is effective in improving the retrieval of treated verbs, but with limited generalization to untreated verbs. Verbs respond very similarly to nouns when treated using the same techniques, but improving verb retrieval may be harder to achieve than improving noun retrieval. The impact on sentence production is more varied. The gains in sentence production are discussed in relation to the different therapy types, the rationale for therapy and the presence of co-occurring sentence difficulties.Conclusions: The review highlights the need for more systematic evaluation of different types of verb therapy, measuring the impact of therapy on verb retrieval, sentence production and connected speech. Only through the judicious assessment and monitoring of change across different contexts will an understanding of how verbs respond to therapy be developed and what generalization patterns can be predicted. This will lead to increased confidence in the selection of therapy approaches for people with verb difficulties in aphasia.